Cancer Patients’ Prehospital Emergency Care: Post Hoc Analysis from the French Prospective Multicenter Study EPICANCER - Peyrony, Olivier (J Clin Med, 2021)
Background: Very little data are available concerning the prehospital emergency care of cancer patients. The objective of this study is to report the trajectories and outcomes of cancer patients attended by prehospital emergency services. Methods: This was an ancillary study from a three-day cross-sectional prospective multicenter study in France. Adult patients with cancer were included if they called the emergency medical dispatch center Service d’Aide Médicale Urgente (SAMU). The study was registered on ClinicalTrials.gov (NCT03393260, accessed on 8th January 2018). Results: During the study period, 1081 cancer patients called the SAMU. The three most frequent reasons were dyspnea (20.2%), neurological disorder (15.4%), and fatigue (13.1%). Among those patients, 949 (87.8%) were directed to the hospital, among which 802 (90.8%) were directed to an emergency department (ED) and 44 (5%) were transported directly to an intensive care unit (ICU). A mobile intensive care unit (MICU) was dispatched 213 (31.6%) times. The decision to dispatch an MICU seemed generally based on the patient’s reason for seeking emergency care and the presence of severity signs rather than on the malignancy or the patient general health status. Among the patients who were directed to the ED, 98 (16.1%) were deceased on day 30. Mortality was 15.4% for those patients directed to the ED but who were not admitted to the ICU in the next 7 days, 28.2% for those who were admitted to ICU in the next 7 days, and 56.1% for those patients transported by the MICU directly to the ICU. Conclusion: Cancer patients attending prehospital emergency care were most often directed to EDs. Patients who were directly transported to the ICU had a high mortality rate, raising the question of improving triage policies.